Il sinodo delle culture, o del multiculturalismo nella verità dell’uomo - Vito Serritella (Democrazia e Diritti Sociali)
By knowing your own history, you can find self-identity and empathy with others, those who are different from yourself. By looking at the mistakes made in history, we learn to accept others with mercy, in truth, and we become capable of forgiving politically to achieve peace.